Case study in erosion control at Mcconnell Air Force Base: redcedar streambank revetments, macroinvertebrates bio assessment, and runoff estimation - Serrano Mora, Jorge Guillermo (Kansas State University, 2024)
Water bodies are crucial ecosystems, they facilitate natural processes that create favorable conditions for biodiversity. This study aims to monitor and document the overall health condition of the watershed at McConnell Air Force Base in Wichita, Kansas, and assess the effectiveness of implementing redcedar revetments on the streambank to mitigate accelerated streambank erosion. The impact of the revetments was evaluated by measuring erosion and deposition rates periodically through rebar pins, conducting a bioassessment using macroinvertebrates, and the impact of impervious surfaces have on the creek with a runoff estimation. To measure erosion and deposition rates, vertical transects containing pieces of rebar were inserted into the eroding bank, with exposed rebar length or burial depth indicating the extent of erosion or deposition. Macroinvertebrate populations were sampled as they are indicators of water quality, habitat quality, and diversity. Various indices were calculated to estimate water quality, species richness, and biodiversity. The runoff estimation was conducted to document high percentages of impervious surfaces which can affect the infiltration and discharge of the nearby stream, and which conservation practices can mitigate. This research compared the results of two revetments previously monitored in a study by Molina (2021) and two recently added for this case study. Redcedar revetments effectively reduced erosion rates and captured sedimentation, enhancing streambank stability over time. Macroinvertebrate sampling reveals improved habitat quality, with revetments supporting increased species diversity. Visual evidence highlights vegetated areas and wildlife presence, while implementing practices like rain gardens can further mitigate erosion and pollution from runoff.
Keywords: Redcedar; Revetment; Erosion; Macroinvertebrate; Runoff; Sediment